2021
DOI: 10.1186/s13063-020-04962-3
|View full text |Cite
|
Sign up to set email alerts
|

ICan, an Internet-based intervention to reduce cannabis use: study protocol for a randomized controlled trial

Abstract: Background Heavy cannabis use is associated with adverse physical and mental health effects. Despite available effective treatments, the majority of heavy cannabis users does not seek professional help. Web-based interventions can provide an alternative for cannabis users who are reluctant to seek professional help. Several web-based cannabis interventions are effective in reducing cannabis use; however, the effect sizes are typically small and attrition rates are typically high. This suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Whether this flexibility will be beneficial toward app use and utility in the context of young adults with psychosis and CUD remains to be determined. To evaluate our approach, we will conduct exploratory subgroup analyses based on participants’ compliance with the recommended frequency of 2 modules per week [ 72 ] and assess differences in cannabis use outcomes and satisfaction with iCC.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this flexibility will be beneficial toward app use and utility in the context of young adults with psychosis and CUD remains to be determined. To evaluate our approach, we will conduct exploratory subgroup analyses based on participants’ compliance with the recommended frequency of 2 modules per week [ 72 ] and assess differences in cannabis use outcomes and satisfaction with iCC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study conducted to explore psychosocial predictors of addictive behaviors between Internet use and Cannabis use found that most participants were males aged over 20 [28]. Evidence denotes that excessive heavy Cannabis use among youth and middle-aged individuals is associated with several adverse health effects on physical and mental faculties [29]. These findings indicate that counseling programs should focus on youth and young generations.…”
Section: Discussionmentioning
confidence: 98%
“…Directly after randomization, the participants assigned to the control condition received a log‐in code to access the on‐line modules. An extensive description of the ICan intervention and the control website can be found in the protocol article [26].…”
Section: Methodsmentioning
confidence: 99%